1995
DOI: 10.1097/00000542-199504000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propofol or Isoflurane Anesthesia on Cardiac Conduction in Children Undergoing Radiofrequency Catheter Ablation for Tachydysrhythmias

Abstract: Neither propofol nor isoflurane anesthesia alter sinoatrial or atrioventricular node function in pediatric patients undergoing radiofrequency catheter ablation, compared to values obtained during baseline anesthesia with alfentanil and midazolam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 10 publications
4
43
1
Order By: Relevance
“…The authors concluded that propofol did not promote significant changes of the electrophysiological parameters of the AV node, which was similar to the results observed by Sharpe et al 24 and Lavoie et al 25 . Those findings do not show evidence that propofol could have a direct action on the electrophysiological properties of the AV node in patients with AVNRT.…”
Section: Studies In Humanssupporting
confidence: 84%
See 2 more Smart Citations
“…The authors concluded that propofol did not promote significant changes of the electrophysiological parameters of the AV node, which was similar to the results observed by Sharpe et al 24 and Lavoie et al 25 . Those findings do not show evidence that propofol could have a direct action on the electrophysiological properties of the AV node in patients with AVNRT.…”
Section: Studies In Humanssupporting
confidence: 84%
“…Two studies that evaluated propofol during anesthesia for EP studies in humans did not demonstrate any direct effect caused by this drug on the activity of the sinoatrial node, and intra-atrial or AV conduction 24,25 .…”
Section: Studies In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated less cardiovascular side effects of propofol on conduction properties of normal and accessory pathways in patients with WPW syndrome during adult EP studies [7][8][9][10][11][12]. One study showed successful use of propofol for EP study for treatment of tachyarrhythmias except for atrial ectopic tachycardia [5,6]. Halogenated anesthetic agents (sevoflurane, isoflurane and desflurane) have resulted in prolongation of the repolarization time of the heart leading to QTc prolongation and induction of arrhythmias in various studies [4,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…The use of anesthetic agents during these pediatric procedures has been well documented and its use is rarely associated with rare lifethreatening cardiovascular adverse events [1]. The cardiovascular side effects associated with the utilization of anesthetic agents include cardiac arrest, desaturation, hypotension, bradycardia/tachycardia, and changes in cardiomyocyte repolarization time (QT prolongation) resulting in arrhythmias [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%